Penerapan Metode Simple Additive Weighting (SAW) Pada Sistem Pendukung Keputusan Pemilihan Jurusan di SMA - Syanzani, Assyifa Aulia; Azrina, Nur; Fitriani, Vika (LPPM STMIK ANTAR BANGSA, 2024)
Major selection in senior high school (SMA) refers to the process by which students select a particular field of study or academic focus to be followed during the senior high school level of education, specifically at the senior high school level. Choosing the right major can also help students better plan and achieve their career goals. The formulation of the problem in this study is how to design a decision support information system for choosing majors in high school using the SAW method. The purpose of this research is to design a decision support information system for choosing majors and apply the SAW method in producing major recommendations for class X students. Based on the results of the recommendation of majors, it is concluded that the majors most recommended to several high school students are Language and Social Sciences majors with a total of 9 students, then Science majors with a total of 7 students who get recommendations for these majors. Recommendations are obtained from calculating the criteria for the Report Card Score and Academic Potential Test of each student for each available major.